PROBLEMATICS OF LITERATION LEARNING ELEMENTARY SCHOOLS IN THE NEW NORMAL ERA - Abidin, Zaenal; Herman, Tatang; Widyasari, Choiriyah; Ismiyasari, Fatimah Nur (PD PGMI se Indonesia, 2021)
This study aims to describe literacy learning problems for elementary school students in the new normal era. This type of research is qualitative research. The research design was a case study at MI Muhammadiyah Kartasura. The subjects of this study were teachers, students, and parents of upper-class students. Data collection techniques with observation, interviews, and documentation. The research data validation was carried out by data triangulation, and analysis technique was carried out using qualitative analysis techniques. The data analysis model uses interactive analysis. The results showed that literacy learning in elementary schools has many problems. It was the difficulty of implementing student literacy habits when studying at home, the low reading interest of students, lack of references owned by teachers, and teachers' mastery in the use of technology. Other problems have come from external, unattractive reading, difficulty accessing reading material, internet signal, and some parents do not have time to assist children in a task. The conclusion of this study is to solve the problem of literacy learning for elementary school students. It requires collaboration between teachers, students, and parents of students and digital literacy that is more creative and innovative to motivate students to read so that they remain productive even though learning from home in the new normal era.